Effects of the Post-Spinal Cord Injury Microenvironment on the Differentiation Capacity of Human Neural Stem Cells Derived from Induced Pluripotent Stem Cells. Issue 10 (October 2016) - López-Serrano, Clara; Torres-Espín, Abel; Hernández, Joaquim; Alvarez-Palomo, Ana B.; Requena, Jordi; Gasull, Xavier; Edel, Michael J.; Navarro, Xavier
Spinal cord injury (SCI) causes loss of neural functions below the level of the lesion due to interruption of spinal pathways and secondary neurodegenerative processes. The transplant of neural stem cells (NSCs) is a promising approach for the repair of SCI. Reprogramming of adult somatic cells into induced pluripotent stem cells (iPSCs) is expected to provide an autologous source of iPSC-derived NSCs, avoiding the immune response as well as ethical issues. However, there is still limited information on the behavior and differentiation pattern of transplanted iPSC-derived NSCs within the damaged spinal cord. We transplanted iPSC-derived NSCs, obtained from adult human somatic cells, into rats at 0 or 7 days after SCI, and evaluated motor-evoked potentials and locomotion of the animals. We histologically analyzed engraftment, proliferation, and differentiation of the iPSC-derived NSCs and the spared tissue in the spinal cords at 7, 21, and 63 days posttransplant. Both transplanted groups showed a late decline in functional recovery compared to vehicle-injected groups. Histological analysis showed proliferation of transplanted cells within the tissue and that cells formed a mass. At the final time point, most grafted cells differentiated to neural and astroglial lineages, but not into oligodendrocytes, while some grafted cells remained undifferentiated and proliferative. The proinflammatory tissue microenviroment of the injured spinal cord induced proliferation of the grafted cells and, therefore, there are possible risks associated with iPSC-derived NSC transplantation. New approaches are needed to promote and guide cell differentiation, as well as reduce their tumorigenicity once the cells are transplanted at the lesion site.